2021
DOI: 10.1159/000513606
|View full text |Cite
|
Sign up to set email alerts
|

Positive Feedback Loop of Long Noncoding RNA OASL-IT1 and Innate Immune Response Restricts the Replication of Zika Virus in Epithelial A549 Cells

Abstract: Expression of host noncoding RNAs and coding mRNAs is significantly altered by viral infection. In the current study, we screened the transcriptional profile of human lung epithelial A549 cells infected with Zika virus (ZIKV) by microarray assay. Seventy-nine long noncoding RNAs (lncRNAs) and 140 mRNAs were differentially expressed (DE). The bioinformatics analysis revealed that the mRNAs adjacent to the DE lncRNAs were closely related to the host responses to viral infection. We selected 7 lncRNAs from the to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 54 publications
(74 reference statements)
0
15
0
Order By: Relevance
“…Accumulating evidence supports the important role of host-encoded lncRNAs in regulating immune response [ 15–17 ]. Some of the recent examples include: lncRNA OASL-IT1 and interferon loop system that regulates antiviral defense against Zika Virus [ 18 ]; lncRNA NLRP3 promotes NLRP3-triggered inflammatory response in early acute lung injury by binding to miR-138-5p [ 19 ]; mRNA-lncRNA crosstalk is involved in immune regulation of carp macrophages [ 20 ]; lncRNA THUMPD3-AS1 is downregulated in osteoarthritis and when overexpressed, it promotes cell proliferation, reduces apoptosis and facilitates inflammatory response [ 19 ]. Besides, host-encoded lncRNAs have also been found to regulate viral infection.…”
Section: Introductionmentioning
confidence: 99%
“…Accumulating evidence supports the important role of host-encoded lncRNAs in regulating immune response [ 15–17 ]. Some of the recent examples include: lncRNA OASL-IT1 and interferon loop system that regulates antiviral defense against Zika Virus [ 18 ]; lncRNA NLRP3 promotes NLRP3-triggered inflammatory response in early acute lung injury by binding to miR-138-5p [ 19 ]; mRNA-lncRNA crosstalk is involved in immune regulation of carp macrophages [ 20 ]; lncRNA THUMPD3-AS1 is downregulated in osteoarthritis and when overexpressed, it promotes cell proliferation, reduces apoptosis and facilitates inflammatory response [ 19 ]. Besides, host-encoded lncRNAs have also been found to regulate viral infection.…”
Section: Introductionmentioning
confidence: 99%
“…LncRNA OASL-IT1 positively regulates IFN-I signaling (81). Silencing of its expression via knockout or knockdown impairs the phosphorylation modification of p38 of mitogenactivated protein kinases (MAPK), IRF3, and NF-kB p65 in response to ZIKA infection (82). The detail of its mechanism is still not understood.…”
Section: General Downstream Cascades For Ifn-i Transcription Activationmentioning
confidence: 99%
“…This complex acts as a scaffold to promote and stabilize the interaction between TRIM25 and the activated RIG-I, and then strengthens TRIM25mediated K63-linked ubiquitination of RIG-I [133]. In epithelial A549 cells, researchers found that lncRNA OASL-IT1 promotes the phosphorylation of p38 MAPK, IRF3, and NF-κB p65, leading to the expression of IFN-β and two classic ISGs (MX1 and IFITM1) in a positive feedback manner during Zika virus (ZIKV) infection [134].…”
Section: Long Non-coding Rnas Promote Antiviral Innate Immune Responsementioning
confidence: 99%